The Influence of Realistic Mathematics Education (RME) on Mathematical Communication Skills of Tenth-Grade Students at SMAN 1 Kuok’s Students - Sari, Resa Aprinita; Hidayat, Adityawarman; Putra, Kasman Edi (RANGE: Jurnal Pendidikan Matematika, 2025)
This research was motivated by the low mathematical communication skills of class X students at SMA Negeri 1 Kuok. One solution to overcome this problem is to use a Realistic Mathematic Education learning approach. This research aims to determine whether or not there is an influence of the Realistic Mathematic Education learning approach on the mathematical communication skills of class X students at SMA Negeri 1 Kuok. This research is a quasi-experimental study using a post-test control group design. The research subjects consisted of classes X.1, totaling 23 students, and X.2, totaling 23 students. The sampling technique used was simple random sampling. The data collection techniques used were observation sheets and mathematical communication ability test questions. The results of this research can be concluded that there is an influence of the Realistic Mathematic Education learning approach on the mathematical communication skills of class X students at SMA Negeri 1 Kuok. This can be proven through the Independent Sample T-Test, obtaining a sig(2-tailed) value of 0.024 < 0.05, so H0 is rejected and Ha is accepted.